Application and mechanisms of metal‐based nanoparticles in the control of bacterial and fungal crop diseases. Issue 1 (21st October 2022) - Li, Yuanbo; Zhang, Peng; Li, Mingshu; Shakoor, Noman; Adeel, Muhammad; Zhou, Pingfan; Guo, Manlin; Jiang, Yaqi; Zhao, Weichen; Lou, BenZhen; Rui, Yukui
Abstract: Nanotechnology is a young branch of the discipline generated by nanomaterials. Its development has greatly contributed to technological progress and product innovation in the field of agriculture. The antimicrobial properties of nanoparticles (NPs) can be used to develop nanopesticides for plant protection. Plant diseases caused by bacterial and fungal infestations are the main types of crop diseases. Once infected, they will seriously threaten crop growth, reduce yield and quality, and affect food safety, posing a health risk to humans. We reviewed the application of metal‐based nanoparticles in inhibiting plant pathogenic bacteria and fungi, and discuss the antibacterial mechanisms of metal‐based nanoparticles from two aspects: the direct interaction between nanoparticles and pathogens, and the indirect effects of inducing plant resilience to disease. © 2022 Society of Chemical Industry. Abstract : Summary of the mechanisms by which nanoparticles induce plant resistance to disease through direct interaction with pathogens and indirect induction of plant resistance.